Pidan Quail Eggs: Comparative Study of the Physicochemical and Sensory Characteristics of Coconut Fibre Ash and Quicklime as Natural Alkalis - Novia, Deni; Melia, Sri; Jamarun, Novirman; Habibburrahman (Jurnal Ilmu-Ilmu Peternakan, 2024)
Pidan eggs can be made into less safe food because of the ingredients used in making them. Coconut fibre ash and quicklime are natural ingredients with alkaline pH values that can be used to make pidan eggs. This research aimed to compare the influence of ash coconut fibre and quicklime yang on egg quail's physicochemical and sensory characteristics. The study employed a methodological approach utilizing a fully randomized design comprising five treatments with four replications each. The treatments involved varying ratios of coconut fibre ash to quicklime: A (90:10), B (70:30), C (50:50), D (30:70), and E (10:90). Diversity analysis revealed that the duration of alkaline fermentation significantly affected (P<0.05) the moisture content, pH value, calcium content, sensory attributes of the albumen and yolk color, and texture. However, it did not significantly impact the aroma of pidan quail eggs. The best research results were a ratio of coconut fibre ash to quicklime of 10:90 with a pH value of 10.53, moisture content of 70.74%, calcium content of 0.51%, sensory value of albumen color of 3.80 (blackish brown), egg yolk color of 4.24 (dark green/dark), aroma of 3.04 (smells of ammonia), and texture of 3.84 (slightly dense).